Challenges and strains in the search for disappeared migrants from Honduras and El Salvador - Martínez-Castillo, Gabriela (2020)
The new uses and meanings of disappearances and the strengthening of restrictive migration policies set the stage for the Central America-Mexico-United States area as the only place in the continent where systematic disappearances of immigrants takes place. Tensions between the State and civil society, as well as with supportive actors and families searching for the disappeared migrants, emerge in this context. This text addresses two specific tensions: a) The debates about how concepts about human rights and legal tools in the search for justice are being used, amplified, and adapted; and b) the conflict between approaches centered on the humanitarian search for justice and those that prioritize judicial processes. The consequences of the implementation of different perspectives on the family committees of disappeared migrants are described throughout the text, as well as the alternatives these families offer to diminish any consequences. This research was constructed with families of disappeared migrants who are activists in committees in El Salvador and Honduras. Salvadorans especially were key interlocutors of this study.  A series of workshops and meetings centered on collective reflection about the informants’ own knowledge took place between 2017 and 2020. This article is based on this exchange of knowledge.